Porous carrier particle and method for manufacturing the same
Patent Information
- Application Number
- JP2024117472
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-16
- Filing Date
- 2024-07-23
- Publication Date
- 2025-02-28
AI Technical Summary
【0023】 本発明の製造方法によれば、従来の方法よりも、簡便に、且つ、効率的に大量のシクロデキストリン金属有機構造体を製造することができる。
Smart Images

Figure 2025027990000023 
Figure 2025027990000024 
Figure 2025027990000025
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal-organic framework and a method for producing the same. [Background technology]
[0002] Metal organic frameworks (MOFs) are known to have a large specific surface area and high thermal and chemical stability compared to conventional porous materials. Among them, MOFs prepared using cyclodextrin (CD) as an organic molecule (cyclodextrin metal organic frameworks (CD-MOFs)) are expected to be used as drug delivery carriers because they show excellent biocompatibility and biodegradability.
[0003] However, conventional methods for producing CD-MOFs, such as the vapor diffusion method and the anti-solvent crystallization method, require a large amount of reaction solvent (e.g., Non-Patent Document 1). Furthermore, in order to obtain a CD-MOF with a high specific surface area using conventional production methods, a washing step for removing unreacted materials and by-products is indispensable. From these perspectives, conventional methods for producing CD-MOFs are not suitable for mass production. In other words, a simple method for efficiently producing a large amount of CD-MOFs has not yet been established.
[0004] Furthermore, the CD-MOF particles obtained by the conventional manufacturing method have an excess of potassium (K + / CD≧2) and is strongly basic, which poses safety issues when administered to the body. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Environmental Chemistry Letters 2023, 21, 447-477. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in consideration of the above-mentioned current state of the prior art, and has as its main object to provide a method for easily and efficiently producing a large amount of cyclodextrin metal-organic frameworks (CD-MOFs). [Means for solving the problem]
[0007] The present inventors have conducted extensive research to achieve the above-mentioned object. As a result, they have found that a cyclodextrin metal organic framework can be obtained simply and efficiently by subjecting a raw material mixture containing cyclodextrin, an alkali metal compound, and a reaction solvent to a mechanochemical treatment. Based on this knowledge, the present inventors have conducted further research and have completed the present invention. That is, the present invention includes the following configurations.
[0008] Item 1. A method for producing a cyclodextrin metal organic framework, comprising: A production method comprising a step of subjecting a raw material mixture containing cyclodextrin, an alkali metal compound, and a reaction solvent to a mechanochemical treatment.
[0009] Item 2. The method according to Item 1, wherein the amount of the alkali metal compound added is less than 2 moles per mole of the cyclodextrin.
[0010] Item 3. The method according to Item 1 or 2, wherein the alkali metal compound is a halide.
[0011] Item 4. The method according to any one of Items 1 to 3, wherein the reaction solvent is an alcohol solvent.
[0012] Item 5. The method according to any one of Items 1 to 4, wherein the amount of the reaction solvent added is 10 mL or less per 1 g of the cyclodextrin.
[0013] Item 6. The method according to any one of Items 1 to 5, which does not include a step of washing the cyclodextrin metal organic framework.
[0014] Item 7. The method according to any one of Items 1 to 6, wherein the cyclodextrin metal organic framework encapsulates a pharmacologically active substance.
[0015] Item 8. A cyclodextrin metal organic framework comprising a cyclodextrin and an alkali metal, wherein the content of the alkali metal is less than 2 moles per mole of the cyclodextrin.
[0016] Item 9. The cyclodextrin metal organic framework according to item 8, which contains a halide ion.
[0017] Item 10. The cyclodextrin metal organic framework according to item 8 or 9, having a median diameter D50 of 10 μm or less.
[0018] Item 11. Specific surface area is 100m 2 / g or more.
[0019] Item 12. The cyclodextrin metal organic framework according to any one of Items 8 to 11, which is in a crystalline form.
[0020] Item 13. The cyclodextrin metal organic framework according to any one of Items 8 to 12, wherein a dispersion obtained by dispersing in an aqueous solvent has a pH of 12 or less.
[0021] Item 14. The cyclodextrin metal organic framework according to any one of Items 8 to 13, which encapsulates a pharmacologically active substance.
[0022] Item 15. The cyclodextrin metal organic framework according to any one of Items 8 to 14, which simultaneously encapsulates both a hydrophilic drug and a hydrophobic drug. Effect of the Invention
[0023] According to the production method of the present invention, a cyclodextrin metal organic framework can be produced in large quantities more simply and efficiently than by conventional methods.
[0024] According to the present invention, it is possible to provide a cyclodextrin metal organic framework that can be safely used as a drug transport carrier. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 is a flow chart illustrating and comparing the production methods of CD-MOF according to the present invention (left side) and the prior art (right side). [Diagram 2] FIG. 1 is a schematic diagram illustrating a method for producing a CD-MOF of the present invention. [Diagram 3] These are powder X-ray diffraction (PXRD) patterns obtained in Example 1. The patterns correspond, from top to bottom, to mechanochemically treated CD-MOFs with K+ / CD=8, 6, 4, 2, 1.5, 1, and 0.67 (Examples 1-7 to 1-1), untreated γ-CD (Comparative Example 1), and a CD-MOF obtained by a vapor diffusion method (Comparative Example 2), respectively. [Figure 4] Powder X-ray diffraction (PXRD) patterns of samples that were not subjected to mechanochemical treatment. The patterns correspond, from top to bottom, to the raw material mixtures with K+ / CD=8, 6, 4, and 2 that were not subjected to mechanochemical treatment, the CD-MOF obtained by the vapor diffusion method, and the untreated γ-CD (Comparative Example 1), respectively. [Diagram 5] 1 shows the adsorption / desorption isotherms obtained in Example 1. [Figure 6] 1 shows the results of thermogravimetric analysis (TGA) performed in Example 1. [Figure 7] Powder X-ray diffraction (PXRD) patterns obtained in Example 2. The patterns correspond to the CD-MOFs obtained using potassium bicarbonate, potassium chloride, potassium acetate, and potassium hydroxide as the potassium source, respectively, from top to bottom. [Figure 8A]1 is an FE-SEM image of a CD-MOF (K+ / CD=2; potassium source: KCl) obtained by the production method of the present invention. [Figure 8B] 1 is an FE-SEM image of a CD-MOF (K+ / CD=2; potassium source: CH3COOK) obtained by the production method of the present invention. [Figure 8C] 1 is an FE-SEM image of a CD-MOF (K+ / CD=2; potassium source: KHCO3) obtained by the production method of the present invention. [Figure 9] 1 shows the adsorption / desorption isotherms obtained in Example 2. [Figure 10] 1 shows the results of thermogravimetric analysis (TGA) performed in Example 2. [Figure 11A] 1 shows the results of a cytotoxicity test carried out in Example 2 on lung cells MRC-5. [Figure 11B] 1 shows the results of a cytotoxicity test carried out in Example 2 on alveolar cells A549. [Figure 11C] 1 shows the results of a cytotoxicity test carried out in Example 2 on small intestinal cells, Caco2. [Figure 12] PXRD patterns obtained in Example 3. The patterns correspond to the CD-MOFs obtained using 2.0, 1.5, 1.0, and 0.5 mL of ethanol, respectively, from the top to the bottom. [Figure 13] PXRD patterns obtained in Example 4. The patterns correspond, from top to bottom, to CD-MOF, potassium chloride, and γ-CD produced by the production method of the present invention with reaction times of 10 minutes and 5 minutes, respectively. [Figure 14] PXRD patterns obtained in Example 5. The patterns correspond, from top to bottom, to CD-MOF, potassium chloride, and γ-CDF produced by the production method of the present invention at reaction temperatures of 80° C. and 60° C., respectively. [Figure 15]3 shows powder X-ray diffraction (PXRD) patterns obtained in Example 6. The patterns correspond, from top to bottom, to the CD-MOFs obtained in Examples 6-10 to 6-1, acetaminophen (ACA), and potassium bicarbonate, respectively. [Figure 16] 1 shows the adsorption / desorption isotherms obtained in Example 6. [Figure 17] 1 shows powder X-ray diffraction (PXRD) patterns obtained in Example 7. The patterns correspond, from top to bottom, to the CD-MOF and levofloxacin (LVFX) obtained in Examples 7-9 to 7-1, respectively. [Figure 18] 1 shows the adsorption / desorption isotherms obtained in Example 7. [Figure 19] PXRD patterns obtained in Example 8. The patterns correspond, from top to bottom, to the CD-MOFs obtained in Examples 8-5 to 8-1, potassium hydrogen carbonate, clotrimazole, and the CD-MOF not encapsulating clotrimazole (Example 1-4), respectively. [Figure 20] 1 shows the adsorption / desorption isotherms obtained in Example 8. [Figure 21] PXRD patterns obtained in Example 9. The patterns correspond, from top to bottom, to the CD-MOF not encapsulating o-ethoxybenzamide (Example 1-4), the CD-MOFs obtained in Examples 9-5 to 9-1, and o-ethoxybenzamide, respectively. [Figure 22] 1 shows the adsorption / desorption isotherms obtained in Example 9. [Diagram 23] This shows the powder X-ray diffraction (PXRD) patterns obtained in Example 10. The patterns correspond, from top to bottom, to potassium bicarbonate, the CD-MOFs obtained in Examples 10-1 and 10-2, o-ethoxybenzamide, acetaminophen (ACA), and the CD-MOF not encapsulating a drug (Example 1-4), respectively. [Figure 24]PXRD patterns obtained in Example 11. The patterns correspond, from top to bottom, to potassium bicarbonate, the CD-MOFs obtained in Examples 11-1 and 11-2, clotrimazole, acetaminophen (ACA), and the CD-MOF containing no drug (Example 1-4). [Diagram 25] Powder X-ray diffraction (PXRD) patterns obtained in Example 12. The patterns correspond, from top to bottom, to the CD-MOFs obtained in Examples 12-1 and 12-2, o-ethoxybenzamide, levofloxacin (LVFX), and the CD-MOF without a drug encapsulated (Example 1-4), respectively. [Figure 26] Powder X-ray diffraction (PXRD) patterns obtained in Example 13. The patterns correspond, from top to bottom, to the CD-MOFs obtained in Examples 13-1 and 13-2, clotrimazole, levofloxacin (LVFX), and the CD-MOF without encapsulating a drug (Example 1-4), respectively. [Figure 27] 1 shows the in vitro inhalation characteristics of the CD-MOFs obtained in Examples 7-5 and 13-1. [Figure 28] 1 shows the in vitro inhalation characteristics of the CD-MOFs obtained in Example 8-5 and Example 13-1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] In this specification, the term "comprise" is a concept that encompasses all of "comprise," "consist essentially of," and "consist only of."
[0027] In this specification, the expression of a numerical range "A to B" means "greater than or equal to A and less than or equal to B."
[0028] In this specification, the term "metal organic framework" refers to a general term for a substance in which a metal and an organic compound form a three-dimensional structure continuously and with regularity and have porosity controlled at the nano level, regardless of whether the substance is in a crystalline or amorphous form.
[0029] 1. Cyclodextrin metal-organic framework The cyclodextrin metal-organic framework of the present invention comprises a cyclodextrin and an alkali metal.
[0030] In addition, the content of the alkali metal in the cyclodextrin metal organic framework of the present invention is less than 2 moles per mole of cyclodextrin. From the viewpoint of stability, the content of the alkali metal is preferably 0.67 moles or more and less than 2 moles per mole of cyclodextrin, more preferably 1.0 moles or more and less than 2 moles, and even more preferably 1.5 moles or more and less than 2 moles. The cyclodextrin metal organic framework having such characteristics is a novel structure not described in the literature, and can be obtained for the first time by the production method of the present invention described later.
[0031] As the cyclodextrin that can be used in the present invention, any cyclodextrin or derivative thereof that is widely known in this field can be used.
[0032] As the cyclodextrin, any of α-cyclodextrin (α-CD), β-cyclodextrin (β-CD), and γ-cyclodextrin (γ-CD) can be used. Among them, β-CD and γ-CD are preferred, and γ-CD is more preferred, because they have large hydrophobic pores.
[0033] The above-mentioned cyclodextrin derivatives include those having a substituent on the hydroxyl group on the glucose constituting the cyclodextrin. Examples of the substituent include an alkyl group having 1 to 10 carbon atoms which may have a hydroxyl group, a sulfonyl group, etc. Examples of the alkyl group having 1 to 10 carbon atoms which may have a hydroxyl group include a methyl group, an ethyl group, a 2-hydroxypropyl group, etc.
[0034] The cyclodextrin or its derivative (hereinafter, these may be collectively referred to as "cyclodextrin") may form an inclusion complex with a guest molecule. As the guest molecule, a wide variety of compounds known as guest molecules can be used depending on the type of cyclodextrin used. In this case, the metal organic framework can encapsulate the guest molecule therein, optionally together with a pharmacologically active substance described below, and can release the guest molecule with the decomposition of the metal organic framework.
[0035] Examples of the alkali metal that can be used in the present invention include lithium, sodium, potassium, rubidium, and cesium. From the viewpoint of safety for the human body, potassium and sodium are preferred, and potassium is more preferred.
[0036] The metal organic framework of the present invention may contain an anion derived from an alkali metal compound that can be used as a raw material. The ion is not particularly limited, and examples thereof include hydroxide ions, halide ions (e.g., fluoride ions, chloride ions, iodide ions, etc.), formate ions, acetate ions, oxalate ions, citrate ions, carbonate ions, borate ions, nitrate ions, phosphate ions, sulfate ions, etc. Among these, acetate ions and halide ions (particularly chloride ions) are preferred as anions contained in the metal organic framework of the present invention from the viewpoint of safety.
[0037] The metal organic framework of the present invention has a polyhedral, preferably cubic, shape. When the metal organic framework of the present invention is obtained by a mechanochemical treatment, it is obtained as an aggregate of fine cubic crystals.
[0038] The median diameter D of the metal-organic framework of the present invention 50 is usually 50 μm or less, preferably 0.1 to 10 μm, more preferably 0.1 to 5 μm, and even more preferably 0.2 to 1 μm. 50 is a value measured by a laser diffraction / scattering method.
[0039] The aerodynamic diameter of the metal organic framework is usually 50 μm or less, preferably 0.1 to 10 μm, more preferably 0.3 to 7 μm, and further preferably 0.5 to 6 μm. The aerodynamic diameter of the metal organic framework is a value calculated by the following formula (1).
[0040]
number
[0041] In the formula, D 50 is the median diameter, ρ P is the particle density, ρ * indicates true density.
[0042] The emitted fraction (EF) of the metal-organic framework is usually 70% or more, preferably 75% or more, more preferably 80% or more, and even more preferably 85% or more. The emitted fraction (EF) of the metal-organic framework is a value calculated by the following formula (2) using an Andersen cascade impactor (ACI).
[0043]
number
[0044] In the formula, total recovered drug indicates the total amount of drug recovered, and emitted dose is the amount of pharmacologically active substance delivered, which indicates the mass of drug released from the capsule.
[0045] The fine particle fraction (FPF) of the metal-organic framework is usually 5% or more, preferably 10% or more, more preferably 20% or more, and even more preferably 25% or more. The fine particle fraction (FPF) of the metal-organic framework is a value calculated by the following formula (3) using an Andersen cascade impactor (ACI).
[0046]
number
[0047] In the formula, emitted dose is the amount of pharmacologically active substance delivered and indicates the mass of drug released from the capsule, and fine particle dose is the fine particle content and indicates the mass of drug that reaches stage 2 or later.
[0048] The extra fine particle fraction (eFPF) of the metal-organic framework is usually 0.1% or more, preferably 1% or more, more preferably 2% or more, and even more preferably 3% or more. The extra fine particle fraction (eFPF) of the metal-organic framework is a value calculated by the following formula (4) using an Andersen cascade impactor (ACI).
[0049]
number
[0050] In the formula, emitted dose is the amount of pharmacologically active substance delivered and indicates the mass of drug released from the capsule, and extra fine particle dose is the extra fine particle content and indicates the mass of drug that reaches stage 5 or later.
[0051] The micropore volume of the metal organic framework of the present invention is typically 1.0 cm 3 / g or less, 0.00001 to 0.30 cm 3 / g is preferable, and 0.0001 to 0.20 cm 3 / g is more preferable, and 0.001 to 0.13 cm 3 In this specification, the term "micropore" refers to a pore having a diameter of 2 nm or less in the metal-organic framework, and the term "micropore volume" refers to the total volume of the micropores in the metal-organic framework.
[0052] The total pore volume of the metal organic framework of the present invention is usually 1.0 cm 3 / g or less, 0.00001 to 0.5 cm 3 / g is preferable, and 0.0001 to 0.40 cm 3 / g is more preferable, and 0.001 to 0.20 cm 3 In this specification, "total pores" means all of the micropores, mesopores and macropores in the metal organic framework, and "total pore volume" means the sum of the volumes of all the pores in the metal organic framework.
[0053] The specific surface area of the metal organic framework of the present invention is usually 100 m 2 / g or more, 100 to 1000m 2 / g is preferable, and 300 to 1000m 2 / g is more preferable, and 500 to 1000m 2 The specific surface area is a value measured by the BET method.
[0054] The bulk density of the metal organic framework of the present invention is usually 1000 mg / cm 3 Less than 1-500mg / cm 3 is preferable, and 10 to 300 mg / cm 3 More preferably, 100 to 250 mg / cm 3 is more preferred.
[0055] The tap density of the metal-organic framework of the present invention is usually 1000 mg / cm 3Less than 1-500mg / cm 3 is preferable, and 10 to 350 mg / cm 3 More preferably, 100 to 300 mg / cm 3 is more preferred.
[0056] The true density of the metal organic framework of the present invention is usually 2000 mg / cm 3 Less than 10-1500mg / cm 3 is preferable, and 100 to 1450 mg / cm 3 More preferably, 1000 to 1410 mg / cm 3 is more preferred.
[0057] The metal organic framework of the present invention can be either crystalline or amorphous. When the metal organic framework is obtained by a mechanochemical treatment, a crystalline metal organic framework is easily obtained.
[0058] When the metal organic framework of the present invention is in a crystalline form, the crystallinity is preferably 70% or more, more preferably 80 to 100%, and even more preferably 90 to 100%. When the metal organic framework of the present invention is in an amorphous form, the crystallinity is preferably less than 30%, more preferably 0 to 20%, and even more preferably 0 to 10%. Here, the "crystallinity" is determined from the powder X-ray diffraction pattern by the formula: crystallinity=crystalline peak area / (crystalline peak area+amorphous peak area)×100%.
[0059] The pH of the dispersion obtained by dispersing the metal organic framework of the present invention in an aqueous solvent is usually 12 or less, and from the viewpoint of safety, it is preferably 5.0 to 9.0, more preferably 6.0 to 8.0, and even more preferably 6.5 to 7.5. Therefore, the metal organic framework of the present invention can be excellent in safety and ease of handling. Here, the aqueous solvent is not particularly limited as long as it is a solvent containing water, but is preferably water.
[0060] The metal organic framework of the present invention has low cytotoxicity, and preferably has no cytotoxicity. Here, the cytotoxicity can be evaluated by using a CCK-8 assay kit for cultured cells. Specifically, a medium (e.g., MEM medium) containing 10% (v / v) of the test solution is added to cells cultured until confluent, and the cells are incubated at 37°C and 5% CO for 24 hours. 2 After culturing in an incubator, the absorbance (for example, measurement wavelength: 450 nm) can be measured using a multiplate reader for evaluation.
[0061] The metal organic framework of the present invention can encapsulate (support) a pharmacologically active substance (drug). Examples of the pharmacologically active substance include pharmacologically active substances used as antifungal drugs, anti-inflammatory drugs, hyperlipidemic drugs, hypertension drugs, and angina pectoris drugs. In addition to the pharmacologically active substances, the metal organic framework of the present invention can also contain active ingredients (active components) that are widely used in the cosmetics or food fields.
[0062] The metal-organic framework of the present invention can encapsulate a hydrophilic drug (a water-soluble drug) or a hydrophobic drug (a poorly water-soluble drug) since the CD-MOF has hydrophilic pores and hydrophobic pores, and can also encapsulate both a hydrophilic drug and a hydrophobic drug simultaneously.
[0063] Examples of the pharmacologically active substances include hydrophilic drugs such as levofloxacin, ofloxacin, garenosaxine methylate, sitafloxacin, flucytosine, and acetaminophen, and hydrophobic drugs such as ibuprofen, ketoprofen, lansoprazole, ketoconazole, celecoxib, fenofibrate, carvedilol, indomethacin, rifampicin, budesonide, clotrimazole, and o-ethoxybenzamide.
[0064] For this reason, the metal organic framework of the present invention is preferably used as a drug transport carrier. The metal organic framework of the present invention can be used as various preparations such as pulmonary preparations, oral preparations, transdermal preparations, and nasal preparations.
[0065] The metal organic framework of the present invention can also be used as a biological imaging probe. In this case, it can encapsulate (support) a wide variety of known imaging probes. Examples of the imaging probe include fluorescent organic molecules for optical imaging, metal nanoparticles, quantum dots, positron-emitting nuclides for positron emission tomography (PET), and contrast agents for magnetic resonance imaging (MRI).
[0066] The content of the pharmacologically active substance in the metal organic framework of the present invention is preferably 0.01 to 70 mass%, more preferably 0.1 to 60 mass%, and further preferably 1 to 50 mass%, based on 100 mass% of the mass of the metal organic framework. The metal organic framework of the present invention is advantageous over conventional metal organic frameworks in that it can encapsulate a large amount of a pharmacologically active substance.
[0067] In addition to being used as a drug transport carrier, the metal organic framework of the present invention is preferably used as an adsorbent, a catalyst carrier, etc. when the specific surface area and pore volume are large.
[0068] In addition to the above components, the metal organic framework of the present invention may contain appropriate additives within the scope of not impairing the effects of the present invention. Examples of additives include surfactants, pH adjusters, polymers, etc.
[0069] 2. Method for producing cyclodextrin metal organic framework The method for producing a cyclodextrin metal organic framework of the present invention is carried out by a mechanochemical method. Specifically, the method for producing the cyclodextrin metal organic framework of the present invention includes a step of subjecting a raw material mixture containing a cyclodextrin, an alkali metal compound, and a reaction solvent to a mechanochemical treatment.
[0070] Mechanochemical processing is a method of grinding and mixing raw materials while applying mechanical energy. According to this method, the raw materials are ground and mixed by applying mechanical impact and friction, so that the raw material mixture comes into vigorous contact and is pulverized, causing a reaction of the raw materials. In other words, mixing, grinding, and reaction occur simultaneously. This makes it possible to react the raw materials more reliably without heating them to high temperatures. By using mechanochemical processing, metastable crystal structures that cannot be obtained by normal heat treatment can be obtained.
[0071] Specifically, the mechanochemical treatment can be carried out by mixing and grinding using a mechanical grinding device such as a ball mill, a bead mill, a rod mill, a vibration mill, a disk mill, a hammer mill, or a jet mill. Of these, the mechanochemical treatment is preferably carried out by mixing and grinding using a planetary ball mill. By using the planetary ball mill, it is possible to produce the cyclodextrin metal organic framework of the present invention by a one-stage milling treatment. In other words, it is useful in terms of simplifying the process, increasing the yield, etc.
[0072] In the production method of the present invention, the raw material mixture may be mixed and then charged into the apparatus, or may be mixed in the apparatus and then subjected to mechanochemical treatment, or may be mixed only after the mechanochemical treatment, but it is preferable that the raw material mixture is mixed and then charged into the apparatus and then subjected to mechanochemical treatment. The raw material mixture may be mixed according to a conventional method.
[0073] The rotation speed during the mechanochemical treatment is not particularly limited, but from the viewpoint of obtaining CD-MOF, it is preferable to carry out the mechanochemical treatment at 1000 rpm or less, more preferably 100 to 800 rpm, and even more preferably 100 to 300 rpm.
[0074] The mechanochemical treatment can be carried out under air or, to suppress side reactions, under a non-oxidizing atmosphere, e.g., Ar, N 2 In an inert gas atmosphere such as H 2The reaction can also be carried out under a reducing atmosphere such as those mentioned above. Furthermore, the reaction can also be carried out under a reduced pressure state in which the oxygen concentration is sufficiently low, for example, a reduced pressure in which the oxygen partial pressure is about 20 Pa or less (particularly 1 to 20 Pa).
[0075] The reaction temperature during the mechanochemical treatment is not particularly limited and is usually 200°C or lower. From the viewpoint of obtaining CD-MOF, the reaction temperature is preferably 100°C or lower, more preferably 80°C or lower, and even more preferably 40°C or lower.
[0076] The reaction time of the mechanochemical treatment is not particularly limited, and the mechanochemical treatment can be performed for any time period that allows CD-MOF to be obtained. The reaction time is usually less than 24 hours, and from the viewpoint of providing a simple production method, it is preferably 60 minutes or less, more preferably 30 minutes or less, and even more preferably 10 minutes or less.
[0077] For example, the mechanochemical treatment can be carried out with an energy amount of about 0.1 to 100 kWh / kg of the raw material mixture within a treatment time range of about 0.1 to 100 hours. Note that this mechanochemical treatment can also be carried out in multiple steps with breaks in between as necessary.
[0078] By the above-mentioned mechanochemical treatment, the target cyclodextrin metal organic framework can be obtained as a fine powder.
[0079] The production method of the present invention thus provides a cyclodextrin metal organic framework, and may then, if necessary, include a step of drying the resulting cyclodextrin metal organic framework, which can further improve the crystallinity.
[0080] The drying step can be carried out according to a conventional method using a desiccator, oven, hot plate, etc. The drying step is not particularly limited, but is preferably carried out by heating to 40 to 100° C., more preferably the heating temperature is 50 to 90° C., and even more preferably 60 to 80° C. The heating time is not particularly limited, but is preferably less than 24 hours, more preferably 10 minutes to 3 hours, and even more preferably 30 minutes to 1 hour.
[0081] When the cyclodextrin metal organic framework thus obtained is used as an adsorbent or a reaction field, it is preferable to make it into a powder molding. There is no particular limitation on the powder molding process, and it can be molded by a known method. For example, it can be obtained by uniaxial pressing at room temperature at 300 MPa using a known powder molding machine.
[0082] The manufacturing method of the present invention is not particularly limited, and may not include a step of isolating and purifying the cyclodextrin metal organic framework obtained by the mechanochemical treatment, and may not include a step of washing. Alternatively, the manufacturing method of the present invention may include an isolation step and / or a washing step within a range that does not impair the object of the present invention. Conventional techniques, such as the vapor diffusion method and the poor solvent crystallization method, involve a crystallization reaction in a solution, so that unreacted substances tend to remain and the specific surface area tends to be low. Therefore, in order to remove the unreacted substances, washing is required to increase the purity of the target product. In order to increase the purity of the target product, an isolation step and / or a washing step are required, and therefore the method is not suitable for mass production. For this reason, the manufacturing method of the present invention is advantageous in that it can easily and efficiently produce a large amount of cyclodextrin metal organic frameworks compared to conventional manufacturing methods.
[0083] Therefore, the production method of the present invention can obtain a cyclodextrin metal organic framework in a high yield. The yield of the production method of the present invention is not particularly limited, and is preferably 90% or more, more preferably 95% or more, further preferably 99% or more, and particularly preferably 100%.
[0084] In the manufacturing method of the present invention, the amount of alkali metal compound (alkali metal) added is not particularly limited. In particular, from the viewpoint of the stability of the cyclodextrin metal organic framework, the amount of alkali metal compound (alkali metal) added is preferably less than 2 moles, more preferably 0.67 moles or more and less than 2 moles, even more preferably 1.0 moles or more and less than 2 moles, and particularly preferably 1.5 moles or more and less than 2 moles, per mole of cyclodextrin. In this case, a novel structure not described in the literature can be presented.
[0085] As the cyclodextrin that can be used in the production method of the present invention, for example, the cyclodextrins mentioned above in "1. Cyclodextrin metal organic framework" can be used.
[0086] In the raw material mixture, the content of cyclodextrin is preferably 15 to 70 mass%, more preferably 20 to 60 mass%, and even more preferably 30 to 50 mass%, based on 100 mass% of the raw material mixture, from the viewpoint of yield.
[0087] Examples of alkali metal compounds that can be used in the production method of the present invention include hydroxides, carbonates, and hydrogen carbonates of alkali metals such as lithium, sodium, potassium, rubidium, and cesium. From the viewpoint of safety for the human body, hydroxides, halides, acetates, and hydrogen carbonates of potassium or sodium are preferred, halides, acetates, and hydrogen carbonates of potassium or sodium are more preferred, and halides and acetates of potassium are even more preferred.
[0088] In the raw material mixture, the content of the alkali metal compound is preferably 0.1 to 50 mass%, more preferably 1 to 30 mass%, and even more preferably 1 to 10 mass%, based on 100 mass% of the raw material mixture, from the viewpoint of yield.
[0089] As the reaction solvent that can be used in the production method of the present invention, a wide variety of known solvents can be used as long as they do not adversely affect the cyclodextrin metal organic framework. Examples of polar solvents include polar solvents such as water, alcohol solvents (e.g., methanol, ethanol), and ether solvents (e.g., 1,4-dioxane, tetrahydrofuran), and non-polar solvents such as alkane solvents (e.g., n-hexane). Among them, from the viewpoint of crystallinity of the metal organic framework, alcohol solvents, ether solvents, and the like are preferred, and alcohol solvents having 1 to 10 carbon atoms such as methanol, ethanol, and propanol are more preferred, and ethanol is even more preferred.
[0090] In the production method of the present invention, the amount of reaction solvent added is usually 100 mL or less per 1 g of cyclodextrin, and from the viewpoint of achieving simple mass production, it is preferably 10 mL or less, more preferably 3.0 mL or less, and even more preferably 1.5 mL or less.
[0091] In the raw material mixture, the content of the reaction solvent is preferably 20 to 80 mass%, more preferably 30 to 70 mass%, and even more preferably 50 to 70 mass%, based on 100 mass% of the raw material mixture, from the viewpoint of yield.
[0092] The amount of cyclodextrin and alkali metal compound added can be determined so that the mixing ratio of these raw materials is the same as the composition ratio of cyclodextrin and alkali metal in the target cyclodextrin metal organic framework. In the conventional technology, the K value is the same as the stoichiometric ratio of the CD-MOF structure regardless of the amount of raw materials added. + In the conventional method, only structures having a composition of / CD=2 can be obtained. However, according to the manufacturing method of the present invention, by changing the amount of addition, it is possible to obtain an arbitrary composition ratio (K + / CD) can be obtained.
[0093] The metal organic framework obtained by the production method of the present invention can encapsulate a pharmacologically active substance. As a method for encapsulating a pharmacologically active substance in the cyclodextrin metal organic framework, it is preferable to include the pharmacologically active substance in the raw material mixture from the viewpoint of increasing the amount of the pharmacologically active substance encapsulated.
[0094] As the pharmacologically active substance that can be used in the production method of the present invention, for example, the pharmacologically active substances mentioned above in "1. Cyclodextrin metal organic framework" can be used.
[0095] The metal organic framework obtained by the production method of the present invention has hydrophilic pores and hydrophobic pores, and therefore can encapsulate (support) hydrophilic and / or hydrophobic drugs. In conventional methods for adsorbing pharmacologically active substances in a liquid phase, even if the metal organic framework has hydrophilic pores and hydrophobic pores, these pores each act as a barrier to the hydrophobic drug or hydrophilic drug, making it difficult to encapsulate both hydrophilic and hydrophobic drugs in the metal organic framework. In contrast, the production method of the present invention is advantageous in that it includes a step of performing a mechanochemical treatment, thereby making it possible to simultaneously encapsulate both hydrophilic and hydrophobic drugs in the obtained metal organic framework.
[0096] The pharmacologically active substance content of the raw material mixture is preferably 0.01 to 200% by mass, more preferably 0.1 to 100% by mass, and even more preferably 1 to 50% by mass, with the sum of the masses of cyclodextrin and alkali metal being 100% by mass. In this case, the metal organic framework of the present invention can encapsulate the pharmacologically active substance at the above content. The production method of the present invention is advantageous over conventional methods in that a large amount of pharmacologically active substance can be encapsulated in the metal organic framework.
[0097] In addition to the cyclodextrin and the alkali metal compound, additives may be added to the raw material mixture as appropriate within the range that does not impair the effects of the present invention. Examples of additives include surfactants, pH adjusters, polymers, etc. EXAMPLES
[0098] EXAMPLES Hereinafter, examples and comparative examples will be shown to more clearly illustrate the features of the present invention, but the present invention is not limited to the following examples.
[0099] [Example 1] Examination of alkali metal content Cyclodextrin metal organic frameworks (CD-MOFs) containing different amounts of alkali metal were produced (Figs. 1 and 2). In the ratios shown in Table 1, γ-CD (0.8670 g), potassium bicarbonate (0.0448 to 0.5354 g), and 2.5 mL (1.86 g) of ethanol were placed in a 250 mL zirconia mill container (FRITSCH) together with 30 zirconia balls (FRITSCH, diameter: 10 mm). Then, mechanical milling was performed at 150 rpm for 10 minutes using a planetary ball mill (PULVERISETTE 6, classic line, FRITSCH). The resulting mixture was dried at 80°C for 1 hour in an oven (ETTAS constant temperature dryer, AS ONE) to obtain CD-MOFs (Examples 1-1 to 1-7). The yield was 100%. In the production method of the present invention, a step of washing the cyclodextrin metal-organic framework was not required to produce high-purity CD-MOF particles.
[0100] As Comparative Example 1, γ-CD that was not subjected to mechanochemical treatment was prepared. Also, as Comparative Example 2, CD-MOF obtained by the conventional vapor diffusion method was prepared. Specifically, in Comparative Example 2, excess methanol (50 mL) in an outer bottle was slowly diffused into an aqueous solution (20 mL) containing 8.0 mM potassium hydroxide and 1.0 mM γ-CD in an inner bottle over a period of 7 days, and then the crystals adhering to the wall of the inner bottle were washed with methanol (80 mL) and dried to obtain CD-MOF (Table 1).
[0101] [Table 1]
[0102] (Powder X-ray Diffraction (PXRD)) The crystal structure of CD-MOF was evaluated using a desktop X-ray diffractometer (MiniFlex 600, Rigaku). The X-ray source was Cu-Kα radiation at 30 kV and 15 mA, with a scanning rate of 4° / min in the 2θ range of 5–60°. The sample was flattened in a well of a glass plate. The obtained powder X-ray diffraction pattern is shown in Figure 3.
[0103] Comparing FIG. 3 with the powder X-ray diffraction pattern (FIG. 4) in the case where the mechanochemical treatment step was not performed, it is clear that the crystallization of CD-MOF was promoted by performing the mechanochemical treatment according to the manufacturing method of the present invention. In FIG. 4, a broad diffraction peak that is an amorphous halo pattern was confirmed near 2θ=20°, while sharp diffraction peaks were confirmed in Examples 1-1 to 1-7 in FIG. 4. Thus, in the manufacturing method of the present invention, K + In the range of / CD = 0.67 to 8, CD-MOFs with crystalline structures were obtained regardless of the ratio of the raw materials mixed. + / CD), in the conventional technology, the stoichiometric ratio of the structure is + In the manufacturing method of the present invention, only a structure having a composition of K / CD=2 can be obtained. + We were able to obtain a CD-MOF with a CD / CD value of <2. + A CD-MOF with / CD<2 has never been reported before, and is the first structure to be produced by the production method of the present invention.
[0104] (Nitrogen gas adsorption method) Nitrogen adsorption / desorption isotherms were evaluated using a BELSORP-max (MicrotracBel) at 77 K. Relative pressure P / P 0 The adsorption isotherm was used to estimate the specific surface area. 0 The adsorption isotherms with α in the range of 0.05 to 0.3 were fitted to the BET equation. sThe total pore volume was calculated using the P / P 0 = 0.99. The measurement results for each sample are shown in FIG. 5 and Table 2. It is clear from FIG. 5 and Table 2 that the production method of the present invention can obtain a CD-MOF having a crystal structure including pores by carrying out a mechanochemical treatment. Furthermore, the production method of the present invention can produce a CD-MOF having a large specific surface area and total pore volume by a method simpler than the conventional technology.
[0105] [Table 2]
[0106] (Thermogravimetric analysis (TGA)) The weight change due to heat treatment of the obtained CD-MOF was measured. The weight at each temperature was evaluated with the weight at 20°C as 100%. The results of the thermogravimetric analysis are shown in Figure 6. + The thermal weight loss was shifted slightly to the higher temperature side as the / CD decreased. + It was found that the stability improved when / CD was small.
[0107] [Example 2] Examination of types of alkali metal compounds Next, the range of potassium sources that can be used in the present invention was examined. CD-MOFs were produced in the same manner as in Example 1, except that the alkali metal compounds shown in Table 3 were used instead of potassium hydrogen carbonate.
[0108] [Table 3]
[0109] (Powder X-ray Diffraction (PXRD)) The powder X-ray diffraction pattern obtained in the same manner as in Example 1 is shown in FIG. +7, it can be said that a CD-MOF having a crystal structure similar to that of Example 1 was obtained even when the potassium source was changed.
[0110] (Field Emission Scanning Electron Microscope (FE-SEM) Observation) Images of the dry powders were randomly taken using a field emission scanning electron microscope (SEM; S-4800, Hitachi High-Tech). The powder samples were fixed to metal stubs with carbon tape and coated with a thin layer of platinum under vacuum conditions (E-1045, Hitachi High-Tech). The measurement conditions were: acceleration voltage: 1.0-3.0 kV, emission current: 10 μA. + The observation images for / CD=2 are shown in Figures 8A-C. When any of the potassium sources was used, particles with a cubic structure were confirmed. Furthermore, the particles were finer and more aggregated than those of conventional techniques such as the vapor diffusion method and the poor solvent crystallization method. In conventional manufacturing methods, only relatively large single crystals can be produced by crystallization, but in the manufacturing method of the present invention, fine CD-MOF particles can be produced by applying a mechanochemical treatment.
[0111] (Nitrogen gas adsorption method) N obtained by the same method as in Example 1 2 The adsorption and desorption isotherms are shown in Figure 9 (K + / CD=2). From the results in Figure 9, it can be said that even when the potassium source was changed, a CD-MOF having a crystal structure including pores similar to that in Example 1 was obtained. It can also be said that there was no significant change in the pore characteristics even when the potassium source was changed.
[0112] (Thermogravimetric analysis (TGA)) The results of thermogravimetric analysis of the obtained CD-MOF are shown in Figure 10. When the potassium source was potassium hydroxide, there was no significant change in thermal stability compared to potassium bicarbonate. On the other hand, when the potassium source was potassium acetate or potassium chloride, the thermal stability was improved compared to potassium bicarbonate.
[0113] (Safety Testing) The CD-MOF obtained by the production method of the present invention was dissolved in purified water to obtain a CD-MOF dispersion with a concentration of about 10 g / L. The pH of each dispersion is shown in Table 4. When potassium hydroxide or potassium bicarbonate was used as the potassium source, the CD-MOF dispersion was basic. On the other hand, when potassium chloride or potassium acetate was used, the CD-MOF dispersion had a pH close to neutral. In other words, the CD-MOF of the present invention can be said to be a safe drug delivery carrier.
[0114] [Table 4]
[0115] (Cytotoxicity test) Lung cells MRC-5 (4×10 5 cells / mL), lung cells A549 (4×10 5 cells / mL) or small intestinal Caco2 cells (confluent) were incubated in MEM medium at 37°C and 5% CO 2 The cells were cultured for 24 hours under the same conditions. A dispersion obtained by dispersing CD-MOF in a medium was added to each well to a final concentration of 0.1 to 20 g / L, and co-cultured with the cells. After 2 hours, the cell activity was evaluated using a CCK-8 assay kit. The activity of the non-additive group was calculated as 100%. The SDS-added group was used as a negative control. The results are shown in Figures 11A to 11C. The CD-MOF obtained by the manufacturing method of the present invention did not show cytotoxicity in the range of a concentration of 10 g / L or less, regardless of which potassium source was used. This shows that the CD-MOF is a material with excellent biocompatibility.
[0116] [Example 3] Consideration of the amount of reaction solvent added The effect of the amount of reaction solvent added was examined. CD-MOFs were produced in the same manner as in Example 1, except that the amount of ethanol added was 2.0 mL, 1.5 mL, 1.0 mL, or 0.5 mL per 0.8670 g of cyclodextrin. The powder X-ray diffraction patterns obtained by the same method as in Example 1 are shown in FIG. 12 (K + / CD=2). From the results in Fig. 12, a relatively broad diffraction peak was obtained when the amount of ethanol added was 0.5 mL, but it can be said that a CD-MOF having a crystal structure similar to that of Example 1 was obtained regardless of the amount of ethanol added. From this, it is clear that the production method of the present invention is a simple method that does not require a large amount of reaction solvent, unlike the conventional technology.
[0117] [Example 4] Reaction time study The effect of reaction time was examined. The reaction time was set to 10 min (potassium source: KCl) or 5 min (potassium source: KHCO 3 CD-MOF was produced in the same manner as in Example 1, except that (K + / CD=1.5). As controls, KCl and untreated γ-CD were used. Powder X-ray diffraction patterns obtained by the same method as in Example 1 are shown in FIG. 13. From the results in FIG. 13, it is clear that a reaction time of 5 minutes is sufficient in the production method of the present invention. This shows that the production method of the present invention is a simple and efficient method that does not require a long reaction time, unlike the conventional techniques.
[0118] [Example 5] Consideration of reaction temperature The effect of reaction temperature was examined. CD-MOF was produced in the same manner as in Example 1, except that the reaction conditions were 80°C for 10 minutes or 60°C for 5 minutes (K + / CD=1.5). As controls, KCl and untreated γ-CD were used. Powder X-ray diffraction patterns obtained by the same method as in Example 1 are shown in FIG. 14. From the results in FIG. 14, it is clear that a reaction temperature of 60° C. is sufficient in the production method of the present invention. This also makes it clear that the production method of the present invention is a simple and efficient method that does not require high temperatures, unlike the prior art.
[0119] [Example 6] Acetaminophen inclusion (carried) A CD-MOF encapsulating (supporting) acetaminophen (ACA) was produced (Examples 6-1 to 6-9). The CD-MOF was prepared in the same manner as in Example 1-4 (K + The amount of cyclodextrin was calculated as 6 moles per mole of CD-MOF.
[0120] [Table 5]
[0121] (Powder X-ray Diffraction (PXRD)) The powder X-ray diffraction pattern obtained by the same method as in Example 1 is shown in Figure 15. From the results in Figure 15, it can be said that a CD-MOF having the same crystal structure as in Example 1 was obtained even when acetaminophen was added.
[0122] (Nitrogen gas adsorption method) N obtained by the same method as in Example 1 2 The adsorption and desorption isotherms are shown in Figure 16. From the results in Figure 16, it can be said that a CD-MOF with a crystal structure containing pores was obtained even when acetaminophen was added.
[0123] (Inclusion amount measurement) The amount of acetaminophen encapsulated in CD-MOF was evaluated. Specifically, CD-MOF was washed with ethanol, and the amount of acetaminophen eluted was quantified. The introduction rate and content of acetaminophen are shown in Table 6. Here, the introduction rate means the ratio of the amount of acetaminophen encapsulated to the amount of acetaminophen added. Furthermore, the content means the ratio (mass ratio) of the amount of acetaminophen to the total mass of CD-MOF. From the results in Table 6, it can be said that acetaminophen was efficiently encapsulated in CD-MOF.
[0124] [Table 6]
[0125] [Example 7] Levofloxacin loading (carrying) CD-MOFs encapsulating (supporting) levofloxacin (LVFX) were produced (Examples 7-1 to 7-9). The CD-MOFs were prepared in the same manner as in Example 1-4 (K + The amount of cyclodextrin was calculated as 6 moles per mole of CD-MOF.
[0126] [Table 7]
[0127] (Powder X-ray Diffraction (PXRD)) The powder X-ray diffraction pattern obtained by the same method as in Example 1 is shown in Figure 17. From the results in Figure 17, it can be said that a CD-MOF having the same crystal structure as in Example 1 was obtained even when levofloxacin was added.
[0128] (Nitrogen gas adsorption method) N obtained by the same method as in Example 1 2 The adsorption and desorption isotherms are shown in Figure 18. From the results in Figure 18, it can be said that a CD-MOF with a crystal structure containing pores was obtained even when levofloxacin was added.
[0129] (Inclusion amount measurement) The amount (content) of levofloxacin encapsulated obtained by the same method as in Example 6 is shown in Table 8. From the results in Table 8, it can be said that levofloxacin was efficiently encapsulated in CD-MOF.
[0130] [Table 8]
[0131] [Example 8] Clotrimazole inclusion (carriage) CD-MOFs encapsulating (supporting) clotrimazole (CTZ) were produced (Examples 8-1 to 8-5). The CD-MOFs were prepared in the same manner as in Example 1-4 (K + The amount of cyclodextrin was calculated as 6 moles per mole of CD-MOF.
[0132] [Table 9]
[0133] (Powder X-ray Diffraction (PXRD)) The powder X-ray diffraction pattern obtained by the same method as in Example 1 is shown in Figure 19. From the results in Figure 19, it can be said that a CD-MOF having the same crystal structure as in Example 1 was obtained even when clotrimazole was added.
[0134] (Nitrogen gas adsorption method) N obtained by the same method as in Example 1 2 The adsorption / desorption isotherms are shown in Figure 20. From the results in Figure 20, it can be said that a CD-MOF having a crystal structure including pores was obtained even when clotrimazole was added.
[0135] (Inclusion amount measurement) The amount (content) of clotrimazole encapsulated obtained by the same method as in Example 6 is shown in Table 10. From the results in Table 10, it can be said that clotrimazole was efficiently encapsulated in CD-MOF.
[0136] [Table 10]
[0137] [Example 9] Inclusion (support) of o-ethoxybenzamide CD-MOFs carrying o-ethoxybenzamide (o-EZD) were produced (Examples 9-1 to 9-5). The CD-MOFs were prepared in the same manner as in Example 1-4 (K), except that o-ethoxybenzamide was added in the amount (molar ratio) shown in Table 11. + The amount of cyclodextrin was calculated as 6 moles per mole of CD-MOF.
[0138] [Table 11]
[0139] (Powder X-ray Diffraction (PXRD)) The powder X-ray diffraction pattern obtained by the same method as in Example 1 is shown in Figure 21. From the results in Figure 21, it can be said that a CD-MOF having the same crystal structure as in Example 1 was obtained even when o-ethoxybenzamide was added.
[0140] (Nitrogen gas adsorption method) N obtained by the same method as in Example 1 2 The adsorption / desorption isotherms are shown in Figure 22. From the results in Figure 22, it can be said that a CD-MOF having a crystal structure including pores was obtained even when o-ethoxybenzamide was added.
[0141] (Inclusion amount measurement) The amount (content) of o-ethoxybenzamide encapsulated obtained by the same method as in Example 6 is shown in Table 12. From the results in Table 12, it can be said that o-ethoxybenzamide was efficiently encapsulated in CD-MOF.
[0142] [Table 12]
[0143] [Example 10] Acetaminophen and o-ethoxybenzamide are contained (supported) A CD-MOF was produced that encapsulates (supports) the hydrophilic drug acetaminophen (ACA) and the hydrophobic drug o-ethoxybenzamide (o-EZD). The CD-MOF was produced in the same manner as in Example 1-4 (K), except that acetaminophen and o-ethoxybenzamide were added in a ratio of 5:5:1 (ACA:o-EZD:CD-MOF). + / CD=2) (Example 10-1). Furthermore, the charge ratio (ACA:o-EZD:CD-MOF) was changed to 3:3:1 to produce CD-MOF (Example 10-2). The charge amount was calculated assuming 6 moles of cyclodextrin as 1 mole of CD-MOF.
[0144] [Example 11] Acetaminophen and clotrimazole are contained (carried) A CD-MOF was produced that encapsulates (supports) the hydrophilic drug acetaminophen (ACA) and the hydrophobic drug clotrimazole (CTZ). The CD-MOF was produced in the same manner as in Example 1-4 (K), except that acetaminophen and clotrimazole were added in a ratio of 5:5:1 (ACA:CTZ:CD-MOF). + / CD=2) (Example 11-1). Furthermore, CD-MOF was produced by changing the charge ratio (ACA:CTZ:CD-MOF) to 3:3:1 (Example 11-2). The charge amount was calculated assuming 6 moles of cyclodextrin as 1 mole of CD-MOF.
[0145] [Example 12] Levofloxacin and o-ethoxybenzamide loading A CD-MOF was produced that encapsulates (supports) the hydrophilic drug levofloxacin (LVFX) and the hydrophobic drug o-ethoxybenzamide (o-EZD). The CD-MOF was produced in the same manner as in Example 1-4 (K), except that levofloxacin and o-ethoxybenzamide were added in a ratio of 5:5:1 (LVFX:o-EZD:CD-MOF). + / CD=2) (Example 12-1). Furthermore, the charge ratio (LVFX:o-EZD:CD-MOF) was changed to 3:3:1 to produce CD-MOF (Example 12-2). The charge amount was calculated assuming 6 moles of cyclodextrin as 1 mole of CD-MOF.
[0146] [Example 13] Levofloxacin and clotrimazole loading A CD-MOF encapsulating (supporting) the hydrophilic drug levofloxacin (LVFX) and the hydrophobic drug clotrimazole (CTZ) was produced. The CD-MOF was prepared in the same manner as in Example 1-4 (K), except that levofloxacin and clotrimazole were added in a ratio of 5:5:1 (LVFX:CTZ:CD-MOF). + / CD=2) (Example 13-1). Furthermore, CD-MOF was produced by changing the charge ratio (LVFX:CTZ:CD-MOF) to 3:3:1 (Example 13-2). The charge amount was calculated assuming 6 moles of cyclodextrin as 1 mole of CD-MOF.
[0147] (Powder X-ray Diffraction (PXRD)) 23 to 26 show the powder X-ray diffraction patterns of the CD-MOFs obtained in Examples 10 to 13. From these results, it can be said that a CD-MOF having a crystal structure similar to that of Example 1 was obtained even when a hydrophilic drug and a hydrophobic drug were added simultaneously.
[0148] (Inclusion amount measurement) The amount of hydrophilic and hydrophobic drugs encapsulated in the CD-MOF was evaluated. 18The determination was performed by high performance liquid chromatography (HPLC; e2695 and 2489; Waters, Milford) equipped with a reversed-phase column (4.6 mm I.D. × 10 mm; Nacalai Tesque, Inc.). The mobile phase used was acetonitrile (phase A) and 0.1% trifluoroacetic acid (TFA) aqueous solution (phase B). The proportion of phase A in the mobile phase was 0 to 3 min: 20%, 3 to 5 min: 30%, and 5 to 10 min: 20%. The detection wavelength was 235 nm, and the flow rate was maintained at 1.0 mL / min. The retention times were 2.5 min (ACA), 3.7 min (LVFX), and 8.3 min (o-EZD). The coefficient of determination of the calibration curve, R 2 The values were in the range of 0.9999 to 1.
[0149] The drug loading (content) in the CD-MOFs obtained in Examples 10 and 12 is shown in Table 13. From the results in Table 13, it can be said that both hydrophilic and hydrophobic drugs could be simultaneously loaded into the CD-MOF.
[0150] [Table 13]
[0151] (in vitro inhalation properties) The in vitro inhalation performance of CD-MOFs was evaluated using an Andersen Cascade Impactor (ACI) (AN-200 system; Tokyo Dylec Corp.) that mimics the human lung. Each sample (10 mg) was inserted into a size 2 hydroxypropyl methylcellulose capsule (Qualicaps). The capsules loaded with the samples were placed in a transpulmonary powder inhaler. The collection plate of each stage was immersed in a 2% (v / v) hexane solution of silicone to generate a silicone layer to reduce particle rebound. A weak inhalation rate (28.3 L / min) was set to simulate patients suffering from respiratory diseases, and the inhalation time was adjusted to achieve a total airflow of 4 L. The proportion of pharmacologically active substances collected in each stage was evaluated by HPLC. The emitted fraction (EF), fine particle fraction (FPF), and extra fine particle fraction (eFPF) were calculated according to the following formulas (2) to (4).
[0152]
number
[0153]
number
[0154]
number
[0155] In each formula, total recovered drug refers to the total amount of drug recovered. emitted dose refers to the amount of pharmacologically active substance delivered, and indicates the mass of drug released from the capsule. fine particle dose refers to the fine particle content, and indicates the mass of drug that has reached stage 2 or later. extra fine particle dose refers to the extra fine particle content, and indicates the mass of drug that has reached stage 5 or later.
[0156] The particle size distributions of the CD-MOFs obtained in Examples 7-5 and 13-1 are shown in Figure 27 and Table 14. The CD-MOFs were used after washing with ethanol and before washing with ethanol. Here, the particle size distribution of the CD-MOFs was determined based on the amount of levofloxacin (LVFX) detected.
[0157] [Table 14]
[0158] The particle size distribution of the CD-MOFs obtained in Examples 8-5 and 13-1 is shown in Figure 28 and Table 15. The CD-MOFs were used after washing with ethanol and before washing with ethanol. Here, the particle size distribution of the CD-MOFs was determined based on the detected amount of clotrimazole (CTZ).
[0159] [Table 15]
[0160] These results indicate that the CD-MOF obtained by the manufacturing method of the present invention has a sufficiently high proportion of particles classified as the fine particle fraction (FPF), which is equal to or higher than that of commercially available powder formulations, making it useful as a pulmonary formulation.
Claims
1. A method for producing a cyclodextrin metal organic framework, comprising the steps of: A production method comprising a step of subjecting a raw material mixture containing cyclodextrin, an alkali metal compound, and a reaction solvent to a mechanochemical treatment.
2. The method according to claim 1 , wherein the amount of the alkali metal compound added is less than 2 moles per mole of the cyclodextrin.
3. The method according to claim 1 or 2, wherein the alkali metal compound is a halide.
4. The method according to claim 1 or 2, wherein the reaction solvent is an alcohol solvent.
5. 3. The method according to claim 1, wherein the amount of the reaction solvent added is 10 mL or less per 1 g of the cyclodextrin.
6. The method for producing the cyclodextrin metal-organic framework according to claim 1 or 2, which does not include a step of washing the cyclodextrin metal-organic framework.
7. The method according to claim 1 or 2, wherein the cyclodextrin metal organic framework encapsulates a pharmacologically active substance.
8. A cyclodextrin metal organic framework comprising a cyclodextrin and an alkali metal, the content of the alkali metal being less than 2 moles per mole of the cyclodextrin.
9. The cyclodextrin metal-organic framework of claim 8 , comprising a halide ion.
10. Median diameter D 50 The cyclodextrin metal organic framework according to claim 8 or 9, wherein the particle size is 10 μm or less.
11. Specific surface area is 100m 2 The cyclodextrin metal organic framework according to claim 8 or 9, wherein the molecular weight of the cyclodextrin metal organic framework is 1000 or more.
12. The cyclodextrin metal-organic framework according to claim 8 or 9, which is in a crystalline form.
13. The cyclodextrin metal organic framework according to claim 8 or 9, wherein a pH of a dispersion obtained by dispersing the cyclodextrin metal organic framework in an aqueous solvent is 12 or less.
14. The cyclodextrin metal organic framework according to claim 8 or 9, which encapsulates a pharmacologically active substance.
15. The cyclodextrin metal-organic framework according to claim 14, which simultaneously encapsulates both a hydrophilic drug and a hydrophobic drug.